The value of neuraminidase inhibitors for the prevention and treatment of seasonal influenza: a systematic review of systematic reviews. - Barbara Michiels; Karolien Van Puyenbroeck; Veronique Verhoeven; Etienne Vermeire; Samuel Coenen (PLoS ONE)
Controversy has arisen regarding the effectiveness of neuraminidase inhibitors (NIs), especially against influenza-related complications. A literature search was performed to critically assess the evidence collected by the available systematic reviews (SRs) regarding the benefits and disadvantages of NIs (oseltamivir, zanamivir) compared to placebos in healthy and at-risk individuals of all ages for prophylaxis and treatment of seasonal influenza. A SR was done using the Cochrane Database of Systematic Reviews, Health Technology Assessment Database, Database of Abstracts of Reviews of Effects, and Medline (January 2006-July 2012). Two reviewers selected SRs based on randomized clinical trials, which were restricted to intention-to-treat results, and they assessed review (AMSTAR) and study quality indicators (GRADE). The SRs included (N = 9) were of high quality. The efficacy of NIs in prophylaxis ranged from 64% (16-85) to 92% (37-99); the absolute risk reduction ranged from 1.2% to 12.1% (GRADE moderate to low). Clinically relevant treatment benefits of NIs were small in healthy adults and children suffering from influenza-like illness (GRADE high to moderate). Oseltamivir reduced antibiotic usage in healthy adults according to one SR, but this was not confirmed by other reviews (GRADE low). Zanamivir showed a preventive effect on antibiotic usage in children (95% (77-99);GRADE moderate) and on the occurrence of bronchitis in at-risk individuals (59% (30-76);GRADE moderate). No evidence was available on the treatment benefits of NIs in elderly and at-risk groups and their effects on hospitalization and mortality. In oseltamivir trials, nausea, vomiting and diarrhea were significant side-effects. For zanamivir trials, no adverse effects have been reported. The combination of diagnostic uncertainty, the risk for virus strain resistance, possible side effects and financial cost outweigh the small benefits of oseltamivir or zanamivir for the prophylaxis and treatment of healthy individuals. No relevant benefits of these NIs on complications in at-risk individuals have been established.